2019
DOI: 10.14710/jvsar.v1i1.4292
|View full text |Cite
|
Sign up to set email alerts
|

Optimization On Subcritical Fluid Extraction Of Zingiberene

Abstract: The establishment of subcritical fluid application for zingiberene extraction was studied by employing water as a green solvent. The zingiberene content was observed by using Liquid Chromatography-Mass Spectrofotometry and regarding to the independent variable of temperature, extraction time, ginger-solvent ratio and aging time. By applying subcritical water, the critical value of zingiberene content obtained was 0.036%.  This value was approached by the surface modeling of alpha for rotatability design which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Statistical analysis was conducted using response surface methodology (RSM) as detailed by Paramita et al (2019). Of the 115 to 135°C temperature range, the best results were obtained at 125°C.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Statistical analysis was conducted using response surface methodology (RSM) as detailed by Paramita et al (2019). Of the 115 to 135°C temperature range, the best results were obtained at 125°C.…”
Section: Discussionmentioning
confidence: 99%
“…Variables that were varied were temperature and reactive extraction time (Paramita et al, 2019). Reactive extraction temperatures were set at 130 and 140°C.…”
Section: Variable Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this process, 0.036% zingiberene was obtained. The complete extraction procedure was conducted at 125 °C, with a ginger-to-solvent ratio of 0.08, an extraction duration of 20 minutes, utilizing water as the environment-friendly solvent, followed by a 9-minute aging period [24] . Another study of ginger extract was reported where gingerol was the active component.…”
Section: Subcritical Fluid Extractionmentioning
confidence: 99%
“…In addition, high temperature above 120℃ can cause the weakening of hydrogen bonds resulting in large amounts of subcritical water ionization products. Subcritical water can also be a catalyst (Paramita et al, 2019). It is caused by weakened hydrogen bonds resulting in the auto-ionization of water into hydronium ion acid catalysts (H3O + ) and hydroxide ion base catalysts (OH -).…”
Section: Introductionmentioning
confidence: 99%